Legislation and legal frame work for sustainable edible insects use in Nigeria - Usman, Habib Sani; Yusuf, Abdullahi Ahmed (International journal of tropical insect science, 2021)
Insects are vital source of protein, and have many advantages as food and feed, when compared to livestock. They are relatively easy to rear and require only small portion of land (mini livestock), uses less water and feed resources, thus saving agricultural land for growing crops and ensuring less emission of greenhouse gases in the atmosphere. However, lack of clear legislation guiding the rearing, consumption and commercialization of edible insects in most countries Nigeria inclusive, hinder the development of edible insects to levels that their potentials could be harnessed for the benefits of the environment, sustainable development and integration as part of a climate smart and or nutrition sensitive agriculture. Here we showed the diversity of edible insects in Nigeria, motivated for enacting legislation on their uses and suggested a pathway to develop the sector by boasting consumer confidence, upscaling, marketing strategies and exports in a sustainable way.